A Karbala Masnevia Writed With The Influence Of Hadîkatu's-Süedâ: Hafid Efendi's Meşhed-i Mihr-i Cemâl - Eren, Hulusi (Abidin Temizer, 2023)
Many works have been written about the Karbala incident in Arabic, Persian and Turkish literature. The works given in Arabic literature under the name of Maktelü'l-Hüseyn constituted the first examples of the genre. VII. the ghazal of Ebu’l-Esved Düvelî (d. 688) is accepted as the first maktel example in the 19th century. The work of Hüseyin Vâiz Kâşifî (d. 1505) has been the most admired among the maktels written in Persian literature. The first maktel known in Turkish literature is the Maktel-i Hüseyn of Yûsuf-ı Meddâh (d. 15th century). Although Lamiî Çelebi's (d. 1532) work is considered more suitable for historical events, Fuzûlî's Hadîkatü's-Süedâ has been the most admired example of this genre in our literature. In the following centuries, many works describing the Karbala event were written in verse, prose and verse-prose in the Anatolian field. One of them is Hafîd Efendi's work called Meşhed-i Mihr-i Cemâl, which he wrote in masnavi verse under the influence of Hadîkatü's-Süedâ. In this study, the mentioned work of Hafîd Efendi was examined. In order to determine the work published by the poet in the Malumat magazine, all the issues of the newspaper were scanned and all the accessible sections were brought together to provide a whole. The effect of Hadîkatü's-Süedâ in the work, which was examined in terms of form and content, was revealed with examples from both works. At the end of the study, the transcript of Meşhed-i Mihr-i Cemâl is included with the transcripts written for the work. Thus, it is aimed to bring another work about the Karbala event into the literature. © 2023, Abidin Temizer. All rights reserved.
HADÎKATÜ’S-SÜEDÂ ETKİSİYLE YAZILAN BİR KERBELÂ MESNEVİSİ: HAFÎD EFENDİ’NİN MEŞHED-İ MİHR-İ CEMÂL’İ
Keywords: Divan Literature; Hafîd Efendi; Karbala; Maktel; Meşhed-i Mihr-i Cemâl